Analisis Faktor -Faktor Yang Mempengaruhi Keputusan Pembelian Pada Produk Minuman Berkarbonasi Coca-Cola (Studi Kasus pada Minimarket dan Sport Centre di Kartasura) - Putra, Robiyansyah, Drs. Sujadi, M.M (2016)
In this study aims to determine the individual (partial) and synchronously (simultaneously) the effect of pricing, product quality, and promotion of their purchasing decisions Coca-cola carbonated beverages (Case Study on Minimarket and Sport Centre Kartasura). The population in this research that people who never buy, consume coca-cola carbonated beverages at the minimarket and sport centers located in the area Kartasura. The sampling method using purposive sampling method selected sample of a population by using specific criteria or considerations. The samples used in the study is that people who are taking the product coca-cola carbonated beverages that were in minimarket and sports center in the surrounding area Kartasura. To facilitate research so that samples taken at random or random as many as 100 respondents. The method of analysis in this study using multiple linear regression analysis and hypothesis testing by t-test, F, and the coefficient of determination (R2). Based on the results of multiple linear regression analysis can be concluded the following research: Results of t test (partial) that the price (X1), Quality of products (X2), and Promotion (X3) has a positive and significant impact on purchasing decisions carbonated beverage coca-cola. The result of F test (simultaneous) that the price (X1), product quality (X2), and Promotion (X3) simultaneously (simultaneously) significantly influence purchasing decisions coca-cola carbonated beverages.